Pengembangan Media Pembelajaran BARA (Bangun Ruang Augmented Reality) Mata Pelajaran Matematika Kelas V SD - Nur Akhmad Fauzi; Unik Ambar Wati; Mely Agustin Rahma Sari; Wiwik Wahidah; Nofian Nur Romadhon (FKIP Universitas Mataram, 2026)
This study aims to develop, determine the quality, and practicality of BARA (Building Augmented Reality Space) learning media in Mathematics for fifth-grade elementary school students. The background of the study is the difficulty of students in understanding abstract mathematical concepts, resulting in low motivation and learning activity. This study uses the Research and Development (R&D) research type with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The developed media utilizes the Assemblr Edu platform to present interactive 3D objects, so that abstract concepts become more concrete and visual. The quality of the media is assessed by material experts and media experts, while practicality is measured through student responses. The validation results from material experts obtained a score of 98.3% (Very Good) and media experts 86.6% (Very Good). Furthermore, the practicality test conducted on 19 fifth-grade students of SDN Wirosaban resulted in a score of 93.1% (Very Practical). These findings indicate that BARA media is a quality and practical learning media. It is concluded that this Augmented Reality spatial media is suitable for use and can be an effective innovative solution to increase students' motivation and understanding of spatial material in Elementary Schools, in line with the demands of 21st century learning